Enantioselective Michael addition of malonates to β, γ-unsaturated α-ketoesters catalysed by Cu(ii) complexes bearing binaphthyl–proline hybrid ligands. Issue 8 (31st January 2023) - Yu, Shibo; Cai, Qihang; Li, Jiahui; Yu, Tianxu; Liang, Jiemian; Jiao, Zilin; Yao, Chao; Li, Yue-Ming
Abstract : Up to 96% yields and up to 92% ee were achieved in enantioselective Michael addition of malonates to β, γ-unsaturated α-ketoesters catalysed by copper(ii ) complexes bearing binaphthyl–proline hybrid ligands. Abstract : High yields (up to 96%) and high ee (up to 92%) were achieved for chiral copper(ii ) complex-catalysed enantioselective Michael addition of malonates to β, γ-unsaturated-α-ketoesters. The chiral ligands took advantage of both the binaphthyl and the proline moieties, and substituents with different electronic and steric features could be tolerated. The reactions could be carried out under mild conditions, and a gram scale reaction could be realised without the loss of yield and enantioselectivity.